Construction of a BDSPHERE solar radiation pressure model for BeiDou GEOs at vernal and autumn equinox periods. Issue 7 (1st October 2018) - Li, Xiaojie; Guo, Rui; Hu, Xiaogong; Tang, Chengpan; Wu, Shan; Chang, Zhiqiao; Liu, Shuai
Abstract: Geostationary Earth Orbit (GEO) satellites are important components of the BeiDou System (BDS). Long-term orbit ephemeris accuracy monitoring in the Operational Control System (OCS) of BDS indicates that the orbit accuracy for the BDS GEOs is unstable and degraded by several meters during the vernal and autumn equinox periods of each year. The SPHERE solar radiation pressure (SRP) model does not do a good job of reflecting the characteristics of the SRP during equinox periods. In view of this problem, this study proposes to replace SPHERE with BDSPHERE for the BDS GEOs during both equinox and non-equinox periods. We smooth the orbits of the BDS GEOs provided in SP3 precise orbit file format of Wuhan University (WHU, Wuhan, China) in the Multi-GNSS Pilot Project (MGEX), re-estimate the SRP parameter over a 2-year period and construct a 2-year continuous time series of the SRP model parameter. By analyzing the time series, a BDSPHERE model is constructed. The polynomial coefficients during the equinox periods are determined based on historical data and new data. Experiments with Beidou data show that during the equinox periods the orbit-only contribution to the signal-in-space range error (SISRE(ORB)) using the BDSPHERE model for GEOs in orbit determination arc and the 8-h and 24-h orbit predictions arc are 0.77, 0.80 and 1.62 m, respectively, which are smaller than those of the conventional SPHERE model by 53%, 60% and 61%, respectively. An evaluation based on global satellite laser ranging (SLR) data shows that during the equinox periods the BDSPHERE model can provide a radial orbit accuracy of 0.61 m, which is 70% better than that of the SPHERE model, and reach the SPHERE model's orbit accuracy in non-eclipsing periods. The BDSPHERE model during equinox periods considerably improves the orbit accuracy and stability of the BDS GEOs. This paper can provide technical support for constructing SRP models for the BDS.